Hubungan Politik Indonesia-Australia Pada Masa Megawati Soekarnoputri - Junaidi, Eko Wahyu (Universitas Pahlawan Tuanku Tambusai, 2024)
The relationship between Indonesia and Australia has experienced various interesting dynamics. One of the lowest points in the relationship between Indonesia and Australia was when one of the provinces in Indonesia, East Timor, broke away from Indonesia. The Indonesian public considers that independence from East Timor is very closely related to Australia's involvement in the process. This has resulted in strained relations between the two countries. Relations between the two countries stretched during the leadership of President B.J. Habibie and continued until the time of President Abdurrahman Wahid. Relations between Indonesia and Australia improved significantly during the leadership of President Megawati Soekarnoputri. Cooperation between the two countries that had stopped running. John Howard is the first world leader to congratulate Megawati Soekarnoputri on her inauguration as president of Indonesia. Keywords: Australia, Indonesia, Megawati, Relationship. Abstrak Hubungan Indonesia dan Australia mengalamai berbagai dinamika yang menarik. Salah satu titik terendah hubungan Indonesia dan Australia ialah ketika salah satu provinsi di Indonesia yaitu Timor Timur melepaskan diri dari Indonesia. Publik Indonesia menilai bahwa kemerdekaan dari Timor Timur sangat erat kaitannya dengan keterlibatan Australia didalam prosesnya. Hal ini berakibat pada hubungan kedua negara yang merenggang. Hubungan kedua negara merenggang pada masa kepemimpinan presiden B.J. Habibie dan berlanjut hingga masa presiden Abdurrahman Wahid. Hubungan Indonesia dan Australia membaik secara signikan pada masa kepemimpinan presiden Megawati Soekarnoputri. Kerjasama diantara kedua negara yang sempat berhenti kemballi berjalan. John Howard ialah pemimpin dunia yang pertama kali memberikan selamat atas pelantikan Megawati Soekarnoputri sebagai presiden Indonesia. Kata Kunci: Australia, Hubungan, Indonesia, Megawati.